Le Néolithique au quotidien Actes du XVIe colloque interrégional sur le Néolithique - Jean-Claude, Blanchet; Alain, Bulard; Claude, Constantin; Daniel, Mordant; Jacques, Tarrête (Documents d'archéologie française, 1993)
Within the framework of conferences dedicated to the neolithic period, the 16th meeting which took place in 1989 (Archaeology Year), was oriented towards the general public rather than professionals. It was organised to expose recent results of research on daily life, in particular settlements, food production, the environment, techniques concerning ceramic production and the working of bone and lithic material. If specialists can find in these important publications precisions such as the caracterisation of the Blicquy group, the non-specialist can discover the impact of man on the mediterranean forest and the environment of western Armonica; and amongst others, a panorama of the bone industry up to the Bronze age. This diversified approach is a witness to the dynamism ans the quality of recent research on the Neolithic.